Introduction - Michael Scriven (The Evaluation Center at Western Michigan University, 2007)
The seventh issue of this journal is going online tomorrow, and contains a number of papers on methodological issues as well as reports from around the globe that tell us about the progress of evaluation in distant lands--in this issue, there are contributions from Ireland, China, the South Pacific, Australasia, and one with ten authors from the 'newly independent states' (ex-USSR).